E-Judiciary: Keabsahan Pemeriksaan Saksi Virtual Dalam Sistem Peradilan Modern - Khatimah, Husnul (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
The development of information technology has driven modernization across various sectors, including the judicial system. One of the innovative implementations is E-Judiciary, the use of electronic technology in the trial process, including virtual witness examinations. This article aims to analyze the legal validity of virtual witness examinations within the modern judicial system in Indonesia, highlighting the legal foundations, principles of justice, and challenges faced. Based on normative analysis, the validity of virtual witnesses is supported by various regulations, such as Article 184 of the Criminal Procedure Code (KUHAP), Article 5 of Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE), and Supreme Court Regulations (Perma) No. 1 of 2019 and No. 4 of 2020. These regulations recognize testimony given via video conference as valid evidence, provided it meets the principles of justice, such as audi et alteram partem, transparency, and accountability. While providing benefits such as time and cost efficiency, the implementation of virtual witnesses faces challenges such as technological readiness, data security, and the validity of witness identity. The conclusion of this article emphasizes that virtual witness examinations are a progressive step in judicial modernization but require support in terms of technological infrastructure and more mature regulations to ensure substantive justice for all parties.